IMPROVING THE ACCOUNTING PERFORMANCE OF RECEIVABLES ON THE TEST BALANCE SHEET: https://doi.org/10.5281/zenodo.15382548 - Safarov , Otabek (Journal of Contemporary World Studies, 2025)
In this article, Accounts Receivable includes claims on other companies’ money, goods, services, and other non-monetary assets. Accounts receivable are divided into current and long-term, depending on the maturity of the accounts receivable and the expected date of collection. Typically, accounts receivable are supported by invoices. The balance sheet item “Promissory Notes Receivable” is supported by official debt obligations.